2018
DOI: 10.3390/ijms19124013
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of 2,3,5,4′-Tetrahydroxystilbene-2-O-β-d-Glucoside in the OVA-Induced Asthma Mice Model

Abstract: Asthma is an inflammatory disease caused by an imbalance of Th1 and Th2 cells. In general, asthma is characterized by a stronger Th2 response. Most conventional asthma treatment focuses on improving airway flow or suppression of airway inflammation. To reduce the side effects of currently used asthma medicines, we have conducted studies on natural products that have no side effects. 2,3,5,4′-tetrahydroxystilbene-2-O-β-d-glucoside (TSG), the main compound of Polygonum multiflorum (PM), has various biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Stilbenes, mainly 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG), possessed antioxidative, antitumor, anti-inflammatory, endothelial protective, neuroprotective, and liver-protective activities, etc. [10][11][12][13][14][15][16][17][18][19][20][21]. Anthraquinones were reported to possess many biological activities, including immunomodulating, anticancer, antimutation, antibacterial, anticancer, antioxidant, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Stilbenes, mainly 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG), possessed antioxidative, antitumor, anti-inflammatory, endothelial protective, neuroprotective, and liver-protective activities, etc. [10][11][12][13][14][15][16][17][18][19][20][21]. Anthraquinones were reported to possess many biological activities, including immunomodulating, anticancer, antimutation, antibacterial, anticancer, antioxidant, etc.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5,4′-tetrahydroxystilbene-2-O-β-d-glucoside (THSG), the main compound of Polygonum multiflorum, has various biological activities, including anti-inflammatory and antioxidant activities. Hwang et al [ 50 ] examined the effects of THSG on Th2 immune responses in an OVA-induced asthma animal model. This study confirmed the potential of THSG in asthma treatment through the modulation of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The OVA-induced asthma mouse model was established according to a previously described method [ 17 ]. Briefly, animals were divided randomly into 6 groups: control (Con) group, model (Mod) group, PLE 100 mg/kg group, PLE 200 mg/kg group, PLE 400 mg/kg group, and Dex 0.5 mg/kg [ 18 ] group. On days 1, 7, and 14, mice in the model group and experimental groups were sensitized with intraperitoneal injection of 30 μ g OVA adsorbed in 1 mg aluminum hydroxide gel [ 19 ].…”
Section: Methodsmentioning
confidence: 99%